2,4-diamino-9H-pyrimido[4,5-b]indol-5-ols: Synthesis, in vitro cytotoxic activity, and QSAR investigations - Dotzauer, Bernd; Grunert, R; Bednarski, P. J.; Lanig, Harald; Landwehr, Jens; Troschütz, Reinhard (Bioorganic & Medicinal Chemistry, 2006)
A series of novel 2,4-diaminopyrimido[4,5-b]indol-6-ols has been synthesized and the in vitro cytotoxic activities were evaluated against four human cancer cell lines originating from solid tumors. An increase in activity was observed when a heteroaromatic ring was annulated on side g of the pyrimido[4,5-b]indole system to give compounds with activities comparable to ellipticine and cisplatin. To understand the experimental cytotoxic activities, QSAR investigations were performed, which showed a very good linearity between the experimental and predicted IC50. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: ellipticine analogues; Nenitzescu reaction; cytotoxicity; QSAR

Clozapine derived 2,3-dihydro-1H-1,4- and 1,5-benzodiazepines with D4 receptor selectivity: synthesis and biological testing - Troschütz, Reinhard; Gmeiner, Peter; Hübner, Harald; et al. (Bioorganic & Medicinal Chemistry, 2004)
Novel 4-arylpiperazin-1-yl-substituted 2,3-dihydro-1H-1,4- and 1H-1,5-benzodiazepines and their aza-analogues were synthesized as debenzoclozapine derivatives for evaluation as potential D4-ligands. While Ki values of some of the title compounds came within the range of clozapine, they showed an impressively greater selectivity over other dopamine receptor subtypes, especially D2. For the most promising compounds, intrinsic activity and binding properties to serotonin 5-HT1A and 5-HT2 were also determined. © 2004 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2004.nat.dchph.lphch.clozap

Design, synthesis and dopamine D4 receptor binding activities of new N-heteroaromatic 5/6-ring Mannich bases - Linz, Sabine; Müller, Jörg; Hübner, Harald; Gmeiner, Peter; Troschütz, Reinhard (Bioorganic & Medicinal Chemistry, 2009)
A series of phenylpiperazine-methyl-substituted 1H-pyrrolo[2,3-c]pyridine, imidazo[1,2-c]-, pyrrolo[2,3-d]- and pyrrolo[3,2-d]pyrimidines were prepared as selective dopamine D4-ligands. The pyrrolo[2,3-d]pyrimidine derivatives 12d (K = 1,9 nM) and 34d (K = 2,4 nM) as well as the pyrrolo[3,2-d]pyrimidine Mannich base 49f (K = 2,8 nM) showed high dopamine D4 receptor activity superior to the atypical antipsychotic agent clozapine. © 2009 Elsevier Ltd. All rights reserved.

Phenylpiperazinylmethylindolecarboxylates and Derivatives as Selective D4-Ligands - Troschütz, Reinhard; Gmeiner, Peter; Hübner, Harald; et al. (Bioorganic & Medicinal Chemistry, 2002)
Novel phenylpiperazinylmethylindolecarboxylates were synthesized for evaluation as potential D4-ligands. Test compounds showed high affinity for the human dopamine D4 receptor and great selectivity over the other receptor subtypes. Intrinsic effects of indole derivatives, which indicated most promising binding properties, were investigated in a mitogenesis assay. © 2002 Elsevier Science Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2002.nat.dchph.lphch.phenyl

Structural variations of piritrexim, a lipophilic inhibitor of human dihydrofolate reductase: synthesis, antitumor activity and molecular modeling investigations. - Zink, Mario; Lanig, Harald; Troschütz, Reinhard (European Journal of Medicinal Chemistry, 2004)
Piritrexim (PTX) (1), a lipophilic inhibitor of the human dihydrofolate reductase, has been evaluated as an anticancer agent. The synthesis of four structural variations (2-5) of PTX is reported. The PTX analogues 2-5 were obtained by reaction of suitable C3-building blocks with pyrimidine-2,4,6-triamine (14) or with cyanacetamide (7) and guanidine (10). The evaluation of 2-4 for antitumor activity against a panel of 60 human cancer cell lines showed inhibitory effects on the growth of the cell lines. These data are supported by molecular modeling and docking studies, which show that compounds 2-4 share the same binding mode within the DHFR active site. Moreover, the estimated ligand binding energies are in good agreement with the experimental activity data.